2005
DOI: 10.1016/s0210-4806(05)73225-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos quirúrgicos en los terceros y cuartos retrasplantes renales

Abstract: Three and four renal transplant survival rates are shorter than first and second ones. Iterative access through lumboiliac incision is associated with a higher vascular complication rate, probably in these patients a transperitoneal access would be better. Multicentric studies with higher numbers of patients are needed to define more clearly which patients would benefit from multiple kidney retransplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Comparing to other studies, our rate is considerably high. Loupy et al [14] noted a 41% complication rate while Gutierrez Baños et al [17] and Mazzucchi et al [18], reported 12.8 and 9.5% rates, respectively. Izquierdo et al [12] reported an overall complication rate of 25.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to other studies, our rate is considerably high. Loupy et al [14] noted a 41% complication rate while Gutierrez Baños et al [17] and Mazzucchi et al [18], reported 12.8 and 9.5% rates, respectively. Izquierdo et al [12] reported an overall complication rate of 25.5%.…”
Section: Discussionmentioning
confidence: 99%